Hadith Review on Beauty: A Living Sunnah Study of Calligraphy as a Medium in Prospering the Mosque in Banyuanyara Village, Sanrobone District, Takalar Regency - Radhie Munadi,; Rayyn, I Gusti Bagus Agung Perdana; Fathur Rahman Al-Fikri, (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This study describes the public perception and implementation of living sunnah values towards the hadith about the beauty of calligraphy as a medium in prospering the mosque in Banyuanyara Village, Sanrobone District, Takalar Regency. The analytical knife used in this research is living sunnah, using a descriptive qualitative method to explore the implementation of living sunnah in the community. The results showed that the community has different perceptions regarding calligraphy in the mosque. Some people think that calligraphy is not important because the essence of a mosque is a place of worship; the most important thing is the comfort of the mosque for worship. However, some people also think that calligraphy is an important component of the mosque as a form of beautifying the mosque and providing visual comfort to the congregation. The implementation of living sunnah values towards the object of research, namely: calligraphy as a medium for da'wah, reading the Qur'an in a mosque that has calligraphy can provide psychological calm to the congregation, and as an effort to understand the verses of Allah swt indirectly with the calligraphy in the mosque.